Government of Assam Annual Plan and Budget-Link 1970-71 - Government of Assam (Government of Assam, 1970)
The Annual Plan and Budget for 1970-71 by the Planning and Development Department of Assam outlines a comprehensive framework for socio-economic development across multiple sectors. The plan allocates significant resources to agriculture (Rs. 648.0 lakhs), animal husbandry, dairying, forestry, fisheries, infrastructure (Rs. 432.43 lakhs), and education (Rs. 346.75 lakhs), alongside centrally sponsored schemes in health, welfare of backward classes, and social development. Emphasizing self-reliance, inclusive growth, and environmental sustainability, the plan integrates education with employment opportunities and prioritizes healthcare, housing, and transport infrastructure to improve accessibility. Additionally, budget provisions for the Assam Government Press highlight investments in administrative capacity and public information dissemination. Overall, the plan reflects a holistic development strategy aimed at enhancing living standards, promoting equitable growth, and strengthening institutional effectiveness for long-term socio-economic progress in Assam.
Planning and Development Department
Planning and Development Department
Keywords: State Plan; Assam; Planning and Development; Budget Allocation; Agriculture; Education; Health Services; Infrastructure; Rural Development; Housing; Public Works; Socio-Economic Development